Fitoremediasi Dan Potensi Tanaman Apu-Apu (Pistia stratiotes L.) Untuk Mengurangi Kadar Logam Tembaga (Cu) Dan Timbal (Pb) Pada Limbah Cair Laboratorium - Anita Karunia Zustriani (Integrated Lab Journal, 2020)
Research on the absorption and accumulation of copper and lead metals in laboratory wastewater has been conducted. The purpose of this research was to provide solutions on handling and processing of heavy metal waste in the laboratory. The phytoremediation method was used for this purpose, using the apu-apu plant as a hyperaccumulator plant. The absorption and accumulation of copper and lead metals happened faster on the beginning of the phytoremediation process. After the phytoremediation process, decrease in copper metal concentration on the fifth day was 85,58% and decrease in lead metal concentration was 79,55%.